Contrasting Patterns of Single Nucleotide Polymorphisms and Structural Variation Across Multiple Invasions. (23rd February 2023) - Stuart, Katarina C; Edwards, Richard J; Sherwin, William B; Rollins, Lee A
Abstract: Genetic divergence is the fundamental process that drives evolution and ultimately speciation. Structural variants (SVs) are large-scale genomic differences within a species or population and can cause functionally important phenotypic differences. Characterizing SVs across invasive species will fill knowledge gaps regarding how patterns of genetic diversity and genetic architecture shape rapid adaptation under new selection regimes. Here, we seek to understand patterns in genetic diversity within the globally invasive European starling, Sturnus vulgaris . Using whole genome sequencing of eight native United Kingdom (UK), eight invasive North America (NA), and 33 invasive Australian (AU) starlings, we examine patterns in genome-wide SNPs and SVs between populations and within Australia. Our findings detail the landscape of standing genetic variation across recently diverged continental populations of this invasive avian. We demonstrate that patterns of genetic diversity estimated from SVs do not necessarily reflect relative patterns from SNP data, either when considering patterns of diversity along the length of the organism's chromosomes (owing to enrichment of SVs in subtelomeric repeat regions), or interpopulation diversity patterns (possibly a result of altered selection regimes or introduction history). Finally, we find that levels of balancing selection within the native range differ across SNP and SV of different classes and outlier classifications. Overall, our results demonstrate that the processes that shape allelic diversity within populations is complex and support the need for further investigation of SVs across a range of taxa to better understand correlations between often well-studied SNP diversity and that of SVs.